Prevalence, symptoms and lifestyle aspect of peptic ulcer disease among students of a Nigerian University (African Journal of Biomedical Research, 2022)
Peptic ulcer disease (PUD) may result to frequent illness, absenteeism in classes and consequent poor academic performance but its distribution and management among university students has been poorly studied. This study assessed the prevalence and symptoms of PUD as well as lifestyle and nutritional status of students with PUD. A total of 297 students (48% females and 52% males) were selected using multistage random sampling method. Information on knowledge, lifestyle and dietary habit was obtained via structured questionnaire. The study revealed 7.9% confirmed PUD cases. Students complained of symptoms suggestive of PUD such as bloating (23.7%), nausea (33.8%), burping (32.4%), bloody stool (15.8%) and heart burn (46.4%). About 68.2% of students with PUD had good knowledge of PUD while 44.1% practice healthy lifestyle. About 36.4%, 59.1% and 4.5% of the confirmed cases were underweight, normal and overweight, respectively. There was no significant relationship between knowledge of healthy lifestyle in PUD and nutritional status. Factors that affected the use of good practice in PUD included early morning lectures (81.8%), food vendors opening late (54.5%) and poor meal variety (50%). In conclusion, low prevalence rate of PUD but high occurrence of symptoms related to PUD was found among the students. An appreciable number of students with PUD were underweight and knowledge of healthy lifestyle did not influence nutritional status. Early morning lectures was the greatest challenge faced by undergraduate students living with PUD. Measures should be taken to detect students with PUD and tackle nutritional challenges faced by these students.